EFEK GREEN ACCOUNTING DAN MATERIAL FLOW COST ACCOUNTING TERHADAP FINANCIAL PERFORMANCE - Fatimah, Nurul; Agustina, Yumniati; Setiadi, Iwan (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
NOAA and NASA report global temperatures are rising by 1°C, the period 2010-2019 will be the hottest decade on record. One of the biggest causes of global warming is industrial and household emissions. BPS stated that the industrial and construction sectors are the first energy consumers, consuming around 42.1% of the total final energy consumption in 2022. As a result of the increasing energy demand from industry, it has an impact on the decline of energy and material resources, thus affecting budgets, production and pollution. The purpose of this study is to prove the effect of Green Accounting and Material Flow Cost Accounting on Financial Performance. Quantitative descriptive research design with an associative approach with the object of research, namely cement and metal mineral mining industry companies listed on IDX in 2017-2022. The number of samples in the study were 36 with descriptive statistical data analysis methods, classical assumptions, multiple linear regression, hypothesis and determination. The results of this study prove that: (1)Green Accounting has a partially significant effect on Financial Performance; (2)Material Flow Cost Accounting shows a partially significant effect on Financial Performance; and (3)Green Accounting and Material Flow Cost Accounting simultaneously have a significant effect on Financial Performance. NOAA dan NASA melaporkan suhu global meningkat sebesar 1oC, periode 2010-2019 akan menjadi dekade terpanas selama satu dekade terakhir. Salah satu penyebab terbesar pemanasan global adalah emisi industri dan rumah tangga. BPS menyatakan bahwa sektor industri dan konstruksi merupakan konsumen energi pertama yang mengonsumsi sekitar 42,1% dari total konsumsi energi final pada tahun 2022. Akibat meningkatnya permintaan energi dari industri berdampak pada penurunan sumber daya energi dan material, sehingga mempengaruhi anggaran, produksi dan polusi. Tujuan dari penelitian ini untuk membuktikan pengaruh Green Accounting dan Material Flow Cost Accounting terhadap Kinerja Keuangan. Desain penelitian deskriptif kuantitatif dengan pendekatan asosiatif dengan objek penelitian yaitu perusahaan industri semen dan pertambangan mineral logam yang terdaftar di BEI pada tahun 2017-2022. Jumlah sampel dalam penelitian adalah 36 dengan metode analisis data statistik deskriptif, asumsi klasik, regresi linier berganda, hipotesis dan determinasi. Hasil penelitian ini membuktikan bahwa: (1) Green Accounting berpengaruh signifikan secara parsial terhadap Kinerja Keuangan; (2) Akuntansi Biaya Aliran Material menunjukkan pengaruh signifikan secara parsial terhadap Kinerja Keuangan; dan (3) Green Accounting dan Material Flow Cost Accounting secara simultan berpengaruh signifikan terhadap Kinerja Keuangan.